Capital social e desenvolvimento local : a experiência de Campo do Brito (SE) - Lima Filho, Sebastião Correia de (2010)
Finding a new model of socioeconomic development based on sustainable production processes, with better distribution, justice and duration is one of Brazil s biggest challenges in the beginning of this century. Therefore, it is necessary to continually perform further studies and research that contribute theoretically and empirically to a better understanding and application of the concept social capital and sustainable development. Development as a synonym for economic growth, qualitative improvement of life for the whole community, being the social capital as an instrument that allows and promotes collective welfare. The present work aims to study the correlation between social capital and sustainable development through the experience of the Cooperative of Producers of Cassava Flour of the city of Campo do Brito (SE), known as Coofama that through the presence of social capital and the aid of Banco do Brasil s strategy for Regional Sustainable Development (DRS- Desenvolvimento Regional Sustentável / BB) is initiating a process of social change in the community. Scholarly contributions on social capital and sustainable development are analyzed, seeking to support the conclusions derived from empirical data collected. Notably, however, that research by Robert Putnam on the process of institutional development of regional governments in Italy, held during the 1970s and 1980s, is the main basis of this work. The social capital, guided by the cooperative action, works as a facilitator and catalyst for sustainable development in a community. Thus, we conclude that there is a link between social capital and sustainable development, at least in this particular case.